Biliary peritonitis and term pregnancy - Davidenko, Nicolás; Praderi, Raúl; Melogno, Silvio; Cazabán, Luis (Cirugía del Uruguay, 1974)
After childbirth a patient underwent surgery for choleperitoneum due to permeation. During pregnancy she had suffered from obstructive jaundice. Surgery was performed in an acute phase, 15 litres of biliary liquid were drained from a preperitoneal pouch but the biliary tract, which was not drained, was not perforated. A fortnight later cholelithiasis was suspected, she was re-oper-ated _and a gallstone imbeded in the papilla was removed; this was the determinant cause of both jaundice and choleperitoneum and had possibly been accompanied by acute pancreatitis and backflow caused by Opie's mechanism.